Lassa fever in pregnancy – report of 2 cases seen at the University College Hospital, Ibadan. (2017)
Lassa fever (LF), an acute viral haemorrhagic fever, is an endemic zoonotic viral infection in West Africa countries with up to 15% case fatality rate. Though a rodent-borne infection, it can also be transmitted from person to person during the care of sick relations or more commonly in health care settings as a nosocomial infection. Vertical transmission from mother to child has been documented. We report 2 cases of LF among pregnant women which were managed at the University College Hospital, Ibadan, between September and October 2014. Both patients were in their early 20s with only one surviving the disease. Both had supportive therapy but none had antiviral therapy. This report emphasized the importance of early presentation, high index of suspicion, prompt diagnosis, and early commencement of supportive therapy in the management of patients suspected with LF especially in the era of other viral haemorrhagic infections.